Pengembangan Aplikasi Analisis Sentimen Penerapan PPKM Level 3 - Jonas Ariston Napitupulu (UNIVERSITAS KALBIS, 2024)
This study aims to analyze tweets about the imposition of Community Activity Restrictions (PPKM) level 3 to find the number of positive, negative, and neutral responses by building webbased software to conduct sentiment analysis on tweets data with the keywords “PPKM level 3